Faktor Determinasi Kualitas Laporan Keuangan Pemerintah Desa di Kecamatan Gandrungmangu - Desi Rahmawati; Novi Dirgantari; Iwan Fakhruddin; Dwi Winarni (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Abstract This research aims to determine the effect of village financial system applications implementation, transparency and the quality of village apparatus on the quality of village government financial reports in Gandrungmangu District. Data for this research was collected through primary data sources obtained through distributing questionnaires. Sample selection used purposive sampling technique. The population were 14 villages and the sample used 48 data respondents from 8 villages. Instrument testing was carried out (consisting of validity tests and reliability tests), descriptive statistical analysis, classical assumption tests (normality test, heteroscedasticity test, multicollinearity test) and hypothesis testinga using the SPSS application. The results prove that the implementation of village financial system applications and the village apparatus quality have no effect on the village government financial reports quality, while transparency has a positive effect on the village government financial reportsquality.